Progress in Intelligent Computing Techniques: Theory, Practice, and Applications Proceedings of ICACNI 2016, Volume 2 - Sa, Pankaj Kumar; Sahoo, Manmath Narayan; Murugappan, M.; Wu, Yulei; Majhi, Banshidhar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book focuses on both theory and applications in the broad areas of communication technology, computer science and information security. This two volume book contains the Proceedings of 4th International Conference on Advanced Computing, Networking and Informatics. This book brings together academic scientists, professors, research scholars and students to share and disseminate information on knowledge and scientific research works related to computing, networking, and informatics to discuss the practical challenges encountered and the solutions adopted. The book also promotes translation of basic research into applied investigation and convert applied investigation into practice.
Preface -- Foreword -- Organizing Committee Details -- Table of Contents -- Chapters -- Author Index.
Keywords: Computational intelligence; Artificial intelligence; Telecommunication; Computational Intelligence; Artificial Intelligence; Communications Engineering, Networks